Avaliação do efeito antifibrótico da Relaxina: estudo in vivo e in vitro - Figueiredo, Camila Médici de [UNIFESP] (2016)
Mesangial cells (MC) and its extracellular matrix are relevant to the maintenance of glomerular filtration rate by modulating the surface available for filtration. Under stimuli such as high glucose, MC proliferate and become hypersecretory of matrix proteins and pro-fibrotic factors such as TGFβ1, contributing to glomerular sclerosis. A number of the strategies have been tested in order to reduce the fibrogenic process dependent of TGFβ1 and in this context, the pregnancy related hormone Relaxin (RLX) has been explored due to its antifibrotic capacity. Usually related to pregnancy, RLX was capable to reduce TGFβ1-induced fibrosis, and increase the secretion of metalloproteinases, which degrade matrix proteins. Thus, the objective of this study was to evaluate if high levels of endogenous RLX found during pregnancy would be able to reduce the fibrogenic process induced by unilateral ureteral obstruction (UUO). Pregnant rats, which have high levels of RLX were used. Seven days pregnant rats were submitted to UUO for 7 or 15 days. In addition to the in vivo fibrosis model, we also evaluated an in vitro model using primary mesangial cells cultured from virgin and pregnant rats. MC were cultured from kidney of pregnant and virgin rats, and stimulated with high glucose concentration (30 mM) and/or RLX (100ng/ml) for 48 hours. The Pregnant group showed to be more protected against the effects of UUO with less reduction in creatinine clearance and less interstitial collagen accumulation. In the in vitro model, high glucose stimulated the expression of RLX receptor (Rxfp1), Collagen and TGFβ1 in the Virgin group but had no effect in MC from pregnant rats. Treatment with RLX prevented these changes in Virgin group. Our results suggest that elevated levels of endogenous or exogenous RLX may have a protective role in fibrogenic process.